PENGEMBANGAN PERANGKAT PEMBELAJARAN PRAKTIK AIR CONDITIONING (AC) DENGAN MENGGUNAKAN METODE CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MAHASISWA TEKNIK MESIN UNESA UNTUK MENUMBUHKAN JIWA ENTREPRENUERSHIP - Ari Wibowo, Mohammad; Susila, I Wayan; munoto, munoto (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2015)
Abstract This research is done to know D3's college student ability in praktik AC's interest also develop learning peripheral and measures entrepreneurship's soul (kewirausahaan). This research is executed on September 2014 at Surabaya's Country University by totals respondent 40 college student utilize developmental research types peripherals and dealt out college student response questionnaires. Downloading process utilize peripheral where was validated by pro expert and have at test-driving to know reabilitas instrument and that data analysing to utilize analisis instrument validity, analisis keterlaksanaan is praktik AC's learning, analisis is thoroughness studies, analisis is intreneur's soul and college student response questionnaire. This observational result point out model learning peripheral inkuiri with Contextual Teaching And Learning's approaching (CTL) syllabus 78,57%, GBRP 89,47%, SAP 86,11%, LKM 83,33% and key LKM 76,92 %, handout 77,77 %, LP and LP's key 81,56 %, and specification table 80 %. Analisis thoroughness usufructs to study model learning peripheral floatings Contextual Teaching And Learning (CTL) having complete criterion with thoroughness score studies (individual), and complete klasikal thoroughness with appreciative score essays kognitif's result product 81,25 % reliabilitas's points item essays 0,975> 0,7; essay kognitif's result processes 75 % reliabilitas's points 0,952> 0,7; and essays psikomotorik's result 75 % reliabilitas's points 0,932> 0,7. Analisis assesses melatihkan entrepreneurship's soul has to assess reliabilitas 0,932> 0,7 by melatihkan's thoroughness score entrepreneurship's souls on brazes DOCK 2 75 % complete. Analisis responds college student to praktik AC's learning by use of model CTL to melatihkan entrepreneurship's soul, having percentage point responds positive(+) as big as 83,3 % college student perceive pleasings with learning already being developed and 6,7 % opine that learning with model CTL so-sos. College student perceives pleasing pass an opinion that 87% perceives trick to teach not pall a lot of activity series that menyenaangkan, 87% opine that college student perceives pleasing because of done by observation or outboard learning brazes, 93% college student perceive that on developed learning get speaking chance, issuing opinion or mutually asks to coeval friend and lecturer and in the end 87 % college student perceive that learning feels easier Keywords: Peripheral development, Entrepreneurship , Contextual Teaching and Learning